Community Supervision, Housing Insecurity, and Homelessness. Issue 1 (May 2022) - Augustine, Dallas; Kushel, Margot
In recent decades, the United States has seen the simultaneous rise of mass incarceration and homelessness. The two crises are driven by the same structural factors and interact with one another, exacerbating their detrimental effects in a feedback loop. People under community supervision face many barriers to housing, putting them at high risk of experiencing homelessness in the months following release. People who experience homelessness are at heightened risk of criminal justice involvement for offenses like violating the terms of their community supervision as they engage in survival behaviors in public spaces. This article presents evidence-based approaches to improving housing strategies for reentry populations, preventing homelessness among those in community supervision, and rehousing members of the reentry community experiencing homelessness. It concludes with recommendations for policymakers interested in improving housing outcomes and overall reentry success for people on community supervision.